VILLAGE FUND: A BALANCED SCORECARD APPROACH - Nur Hasanah; Novita Novita (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2019)
In public sector organizations the Balanced Scorecard (BSC) is not only used as a tool to assess current performance, BSC can also be used to determine performance targets in the future. The performance is certainly in the form of public service products that are directly acceptable and felt by the community. In village government as organizations that receive Dana Desa program, the implementation of the BSC must be supported by the application of the Dana Desa principle so that the Dana Desa can be used in accordance with its objectives. The purpose of this study is to assess the performance of Bojong Kulur Village in allocating Dana Desa which can then be used as an evaluation material for a better Bojong Kulur Village performance. Data collection techniques for this study were carried out by observation, documentation, interviews, as well as distributing questionnaires to the community and the Bojong Kulur Village apparatus. The results of this study are the balanced scorecard design that provides strategic initiatives as an action to improve organizational performance that can be used by Bojong Kulur Village as a performance evaluation related to the allocation of Dana Desa to be in accordance with its principles.